Changes in Treg and Breg cells in a healthy pediatric population - Luo, Yiyi; Acevedo, Daniel; Vlagea, Alexandru; Codina, Anna; García-García, Ana; Deyà-Martínez, Angela; Martí-Castellote, Celia; Esteve-Solé, Ana; Alsina, Laia (Frontiers in Immunology, 2023)
The interpretation of clinical diagnostic results in suspected inborn errors of immunity, including tregopathies, is hampered by the lack of age-stratified reference values for regulatory T cells (Treg) in the pediatric population, and a consensus concerning which Treg immunophenotype to use. Regulatory B cells (Breg) are an important component of the regulatory system that have been poorly studied in the pediatric population. We analyzed 1) the correlation between the three immunophenotypic definitions of Treg (CD4+CD25hiCD127low, CD4+CD25hiCD127lowFoxP3+, CD4+CD25hiFoxP3+), and with CD4+CD25hi, and 2) the changes in Treg and Breg frequency and their maturation status with age. We performed peripheral blood immunophenotyping of Treg and Breg (CD19+CD24hiCD38hi) by flow cytometry in 55 healthy pediatric controls. We observed that Treg numbers varied depending on the definition used, the frequency ranging between: 3.3–9.7% for CD4+CD25hiCD127low, 0.07-1.6% for CD4+CD25hiCD127lowFoxP3+ and 0.24-2.83% for CD4+CD25hiFoxP3+. The correlation between the three definitions of Treg was positive for most age ranges, especially between the two intracellular panels and with CD4+CD25hi vs CD4+CD25hiCD127low. Treg and Breg frequency tended to decline after 7 and 3 years onwards, respectively. Treg maturation status increased with age, with a decline of naïve Treg and an increase in memory/effector Treg from age 7 onwards. Memory Breg increased progressively from age 3 onwards. In conclusion, the numbers of Treg frequency span a wide range depending on the immunophenotypic definition used despite a good level of correlation existing between them. The decline in numbers and maturation process with age occurs earlier in Breg than Treg.